Bibliometric analysis of amebiasis research - Ali Cihat Yildirim; Emine Kübra Dindar Demiray; Sevil Alkan (National Scientific Medical Center, 2022)
Aim: Amebiasis is a disease caused by protozoon Entamoeba histolytica, that results in amoebic dysentery. While intestinal parasites are the third leading cause of death, especially in developing countries, it has been of global concern. Bibliometric methods have been used in the parasitology discipline for more than 30 years, however there is not any bibliometric study on amebiasis in the literature. Our aim was to analyse the published literature on amebiasis by bibliometric methods. Material and methods: A systematic evaluation of the literature using the Scopus database was made from inception to 2021. The search terms 'amebiasis', 'Entamoeba', 'Entamoeba histolytica', and 'amoebic dysentery' were used. The authors, publication year, title, publishing country/journal/institution, title, keywords, and citation numbers were acquired for each article. Descriptive data analysis was conducted via Microsoft Excel 2010 and Scopus database's graphics were used. Results: Among 7,140 articles, 18.9 % of them were published open access, and 72.75 % of them were in the English language. Most of the articles were from the area of medicine. The USA, Mexico, and India were the top leading countries. The number of publications did not fall below 50 per year since 1950. There was an increasing number of citations on amebiasis research recently. Conclusion: Amebiasis is a global concern as one of the leading infectious causes of mortality in developing countries. Bibliometric analysis has shown the growing attraction to the amebiasis research, so it will continue to be global public health issue. Key words: amebiasis, bibliometric analysis, Entamoeba histolytica, bibliometrics